Strategi Pemikiran Pendidikan Ibnu Sina Berbasis Teori Al-Nafs dan Relevansinya terhadap Pendidikan Modern - Andi Abd. Muis; Nurul Ilmi Adyana; Jeny Rheka; Muhammad Kharis (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the concept of educational curriculum according to Ibnu Sina and its relevance to the development of Islamic education. The method used is qualitative descriptive research through literature study with a normative and conceptual approach. The results of the study show that Ibnu Sina’s curriculum is designed based on psychological aspects and the developmental stages of students with the theoretical foundation of al-nafs (soul) to develop physical, intellectual, moral, and spiritual potential in a balanced manner. In conclusion, education according to Ibnu Sina is a process of the perfection of the soul (takamul al-nafs) to form insān kāmil. The novelty of this research lies in the integration of developmental psychology concepts in the design of a holistic Islamic education curriculum, while its difference from previous studies is the emphasis on the practical implications of Ibnu Sina’s thought in developing a student-development-based curriculum.